اتجاهات التفكير في علاقة الأخلاق بالدين في الفلسفة الدينية: قراءة في أطروحة طه عبد الرحمن - فريدي, سمير (جامعة الوادي - University of Eloued, 2022)
الملخص يسعى البحث إلى إبراز علاقة الأخلاق بالمسألة الدينية انطلاقا من المنظور الائتماني لفلسفة طه عبد الرحمن، من حيث بيان أيهما يتفرع من الآخر عند الفلاسفة، وذلك من خلال نقد وتحليل اتجاهات التفكير الفلسفي في التنظير التي قارب هذه الثنائية، والتي تولدت عنها ثلاث اتجاهات كبرى : اتجاه يرى أن الأخلاق انبثقت من الدين، واتجاه يرى بأن الدين استكنه من الأخلاق، واتجاه آخر يرى أنه لا مجال للتفريق بين الأخلاق والدين. abstract The research seeks to highlight the relationship of ethics to the religious question In the philosophy of Taha Abdel Rahman, and the statement of which is the one that spans from the other from philosophers, by critical and analyzing the philosophical thinking trends in theorizing the two, which generated three major trends: A trend that believes ethics has emerged from religion, a trend that religion believes has enabled it from morality, and another that sees no distinction between morality and religion.
Thinking trends in the relationship of ethics and religion in religious philosophy- A reading of Taha Abd Arrahman's thesis-
مقال
Keywords: الدين ; الأخلاق ; فلسفة الدين ; طه عبد الرحمن; Religion ; Ethics ; Philosophy of Religion ; Taha Abd Arrahman